Evaluation of the Antioxidant Activity of Ethanol Extract from Terfezia claveryi Harvested from Anbar Desert - Omar, Marwah Abdul Sattar; Jasim, Rusol Mohammed (Iraqi Journal of Science, 2026)
Desert truffles are edible fungi that grow wild in various areas worldwide and are seasonal. The objective of the research is to illustrate the efficacy of the alcoholic extract of Terfezia claveryi as an antioxidant after diagnosing truffle species by polymerase chain reaction (PCR), antioxidant activities were determined by (DPPH) 2,2-diphenyl-1-picrylhydrazyl and (FRAP) ferric ion-reducing antioxidant power, then compared with positive controls. The antioxidant activity of ethanol extract was evaluated using T. claveryi ascocarps which were harvested from Anbar desert, Iraq. The ethanol extract exhibited the highest DPPH radical-scavenging activity compared to ascorbic acid, with IC50 values of 6 µg/ml and 1 µg/ml, respectively. The FRAP assay revealed no significant reducing power at a concentration of 0.16 µg/ml (1.859±0.003), while significant effects were noted at concentrations of 0.64, 0.32, and 0.08 µg/ml. In addition, catalase and peroxidase enzymes have been thoroughly investigated for their antioxidant properties. This study reveals that T. claveryi contains catalase and peroxidase enzymes at concentrations of 0.862 U/mg and 6000 U/mg, respectively. The results indicated that T. claveryi possesses antioxidant properties and may be useful in treating of disorders caused by free radicals.